AeU Offers Graduate Diploma for Practising Preschool Teachers - Borneo, Post (Borneo Post, 2018)
Asia e University's (AeU) School of Education and Cognitive Science is offering the Graduate Diploma in Early Childhood Education which is designed for practising preschool teacher.